Electrode mixture for secondary battery, electrode for all-solid secondary battery, and all-solid secondary battery

JP2025033277APending Publication Date: 2025-03-13NIPPON ELECTRIC GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023138889
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0023】 本発明によれば、電子伝導性及びイオン伝導性を高いレベルで両立することができ、高レート時の電池特性を効果的に向上させることができる、二次電池用電極合材、該二次電池用電極合材を用いた全固体二次電池用電極、及び該全固体二次電池用電極を用いた全固体二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033277000001_ABST
    Figure 2025033277000001_ABST
Patent Text Reader

Abstract

To provide an electrode mixture for a secondary battery, in which both electron conductivity and ion conductivity can be achieved at a high level and the battery characteristics can be improved effectively.SOLUTION: An electrode mixture for a secondary battery includes a positive electrode active material and a conductive auxiliary agent. The positive electrode active material includes (i) at least one kind of transition metal element selected from the group consisting of Cr, Fe, Mn, Co, Ni, Ti, and Nb, (ii) at least one kind of element selected from the group consisting of P, Si, and B, and (iii) an element containing O, and the conductive auxiliary agent includes sheet-shaped carbon.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode mixture for a secondary battery, an electrode for an all-solid-state secondary battery using the electrode mixture for a secondary battery, and an all-solid-state secondary battery using the electrode for an all-solid-state secondary battery. [Background technology]

[0002] Lithium-ion secondary batteries have established their position as high-capacity, lightweight power sources that are essential for mobile devices, electric vehicles, and the like. However, current lithium-ion secondary batteries mainly use flammable organic electrolytes as electrolytes, raising concerns about the risk of fire and other problems. To solve this problem, development of all-solid-state lithium-ion secondary batteries that use solid electrolytes instead of organic electrolytes is underway. In addition, because of concerns about issues with lithium, such as the global rise in the price of raw materials, development of all-solid-state sodium-ion secondary batteries is also underway.

[0003] In the following Patent Document 1, Na x (Fe 1-a M a ) y P2O z (M is at least one transition metal element selected from the group consisting of Cr, Mn, Co, and Ni, 1.2≦x≦2.8, 0.95≦y≦1.6, 0≦a≦0.9, 7≦z≦8), a sodium ion conductive solid electrolyte, and conductive carbon are disclosed. Patent Document 1 describes that acetylene black, which has high electronic conductivity, is preferable as the conductive carbon. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 084573 Summary of the Invention [Problem to be solved by the invention]

[0005] However, even with the positive electrode material for an electricity storage device of Patent Document 1, it is difficult to achieve both high levels of electronic conductivity and ionic conductivity, and there is a problem in that it is still difficult to sufficiently improve the battery characteristics.

[0006] An object of the present invention is to provide an electrode composite for a secondary battery that can achieve both high levels of electronic conductivity and ionic conductivity and effectively improve battery characteristics at high rates; an electrode for an all-solid-state secondary battery that uses the electrode composite for a secondary battery; and an all-solid-state secondary battery that uses the electrode for an all-solid-state secondary battery. [Means for solving the problem]

[0007] Each aspect of an electrode mixture for a secondary battery, an electrode for an all-solid-state secondary battery, and an all-solid-state secondary battery that can solve the above problems will be described.

[0008] The electrode mixture for a secondary battery according to the first aspect of the present invention comprises a positive electrode active material and a conductive assistant, the positive electrode active material comprising: (i) at least one transition metal element selected from the group consisting of Cr, Fe, Mn, Co, Ni, Ti, and Nb; (ii) at least one element selected from the group consisting of P, Si, and B; and (iii) an element consisting of O; and the conductive assistant comprises sheet carbon.

[0009] In the electrode mixture for a secondary battery of Aspect 2, in Aspect 1, it is preferable that the conductive assistant consists of only sheet-like carbon.

[0010] In the electrode mixture for a secondary battery of Aspect 3, in Aspect 1 or Aspect 2, it is preferable that the sheet carbon contains graphene.

[0011] In the electrode mixture for a secondary battery of Aspect 4, in any one of Aspects 1 to 3, it is preferable that the sheet carbon consists of graphene only.

[0012] In the electrode mixture for a secondary battery of aspect 5, in any one of aspects 1 to 4, the positive electrode active material is represented by the general formula A x MC y O z (A is at least one selected from the group consisting of Li and Na, M is at least one selected from the group consisting of Cr, Fe, Mn, Co and Ni, C is at least one selected from the group consisting of P, Si and B, 0.2≦x≦4.2, 0.65≦y≦6.5, and 2.5≦z≦20).

[0013] In the secondary battery electrode mixture of Aspect 6, in any one of Aspects 1 to 5, it is preferable that the positive electrode active material further contains Na.

[0014] In the seventh aspect, in any one of the first to sixth aspects, the electrode mixture for a secondary battery preferably further contains a solid electrolyte.

[0015] In the electrode mixture for a secondary battery of Aspect 8, in Aspect 7, it is preferable that the solid electrolyte contains β-alumina, β″-alumina, or NASICON type crystal.

[0016] In the electrode mixture for a secondary battery of Aspect 9, in any one of Aspects 1 to 8, the electrode mixture for a secondary battery preferably contains, in mass %, 30% to 98% of the positive electrode active material, 0.1% to 65% of a solid electrolyte, and 0.1% to 3% of the conductive assistant.

[0017] In the electrode mixture for a secondary battery of aspect 10, in any one of aspects 1 to 9, it is preferable that the ratio of the content of the conductive assistant to the positive electrode active material (conductive assistant / positive electrode active material) is 0.001 or more and 0.05 or less in mass ratio.

[0018] In the secondary battery electrode mixture of Aspect 11, in any one of Aspects 1 to 10, it is preferable that the ratio of the surface area of ​​the conductive assistant to the positive electrode active material (conductive assistant / positive electrode active material) is 0.01 or more and 0.5 or less.

[0019] In the electrode mixture for a secondary battery of Aspect 12, in any one of Aspects 1 to 11, the electrode mixture for a secondary battery is preferably for a sodium ion secondary battery.

[0020] In the electrode mixture for a secondary battery of Aspect 13, in any one of Aspects 1 to 12, the electrode mixture for a secondary battery is preferably for an all-solid-state sodium ion secondary battery.

[0021] An electrode for an all-solid-state secondary battery according to a fourteenth aspect of the present invention is characterized in that it contains the electrode mixture for a secondary battery according to any one of the first to thirteenth aspects.

[0022] An all-solid-state secondary battery according to a fifteenth aspect of the present invention is characterized in that it includes the all-solid-state secondary battery electrode according to the fourteenth aspect as a positive electrode. Effect of the Invention

[0023] According to the present invention, it is possible to provide an electrode composite for a secondary battery, which can achieve both high levels of electronic conductivity and ionic conductivity and can effectively improve battery characteristics at high rates, an electrode for an all-solid-state secondary battery using the electrode composite for a secondary battery, and an all-solid-state secondary battery using the electrode for an all-solid-state secondary battery. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a solid electrolyte layer and an electrode layer formed thereon according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an all-solid-state secondary battery according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing a solid electrolyte layer and an electrode layer formed thereon, according to the prior art. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Preferred embodiments will be described below. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments. In addition, in each drawing, components having substantially the same functions may be referred to by the same reference numerals.

[0026] [Electrode composite material for secondary batteries] The electrode mixture for a secondary battery of the present invention includes a positive electrode active material and a conductive assistant. The electrode mixture for a secondary battery of the present invention may further include a solid electrolyte. The positive electrode active material includes (i) at least one transition metal element selected from the group consisting of Cr, Fe, Mn, Co, Ni, Ti, and Nb, (ii) at least one element selected from the group consisting of P, Si, and B, and (iii) an element consisting of O. The conductive assistant includes sheet carbon.

[0027] Since the electrode material for secondary batteries of the present invention has the above-mentioned configuration, even when the cathode active material having a very low electronic conductivity is used as an electrode for a secondary battery, it is possible to achieve both high levels of electronic conductivity and ionic conductivity, and to effectively improve the battery characteristics. This point can be explained as follows with reference to Figs. 1 and 3.

[0028] Fig. 1 is a schematic cross-sectional view showing a solid electrolyte layer 2 and an electrode layer 1 formed thereon according to one embodiment of the present invention. The electrode layer 1 is made of an electrode mixture for a secondary battery including a positive electrode active material 3, a solid electrolyte 4, and a conductive assistant 5. The conductive assistant 5 includes sheet-like carbon. The conductive assistant 5 is preferably made only of sheet-like carbon. The solid electrolyte layer 2 mainly includes a solid electrolyte.

[0029] 3 is a schematic cross-sectional view showing a solid electrolyte layer and an electrode layer formed thereon according to the prior art. The electrode layer 101 is made of an electrode mixture for a secondary battery, which contains a positive electrode active material 103, a solid electrolyte 104, and a conductive additive 105 made of acetylene black.

[0030] However, the active material used in the electrodes of all-solid-state secondary batteries generally does not have sufficient electronic conductivity and ionic conductivity. Therefore, in addition to the active material, a solid electrolyte and a conductive assistant are used in the electrodes of all-solid-state secondary batteries. However, if the amount of the conductive assistant is increased to increase the electronic conductivity, the conductive assistant may inhibit ionic conduction, resulting in a decrease in ionic conductivity. Therefore, in conventional all-solid-state secondary batteries, there is a problem that it is difficult to achieve both electronic conductivity and ionic conductivity at a high level.

[0031] In addition, when using a positive electrode active material such as that of the present invention, if the content of the conductive assistant is increased in order to increase the electronic conductivity, the surface of the positive electrode active material precursor powder is covered with the conductive assistant during sintering of the positive electrode active material precursor powder, which results in a decrease in sinterability and a decrease in battery characteristics. In particular, when the thickness of the electrode layer is increased in order to increase the battery capacity, there is a problem that the sinterability is further decreased and the battery characteristics are likely to decrease.

[0032] In contrast, as shown in FIG. 1, the electrode layer 1 made of the electrode mixture for a secondary battery of the present invention has a conductive assistant 5 containing sheet-like carbon. Since the sheet-like carbon contributes more to electronic conduction than acetylene black, the electrode layer 1 made of the electrode mixture for a secondary battery of the present invention is considered to be easier to ensure an electronic conduction path than the electrode layer 101 using the substantially spherical acetylene black shown in FIG. 3. Therefore, the electrode layer 1 made of the electrode mixture for a secondary battery of the present invention can exhibit high electronic conductivity even if the amount of the conductive assistant 5 added is reduced, so that the conductive assistant is less likely to inhibit ion conduction, and the ion conductivity can be increased while maintaining high electronic conductivity. In particular, when the conductive assistant is made of only sheet-like carbon, the above effect is enhanced.

[0033] In addition, since the electrode mixture for secondary batteries of the present invention can reduce the amount of conductive assistant 5 added, even when the positive electrode active material of the present invention is used, the sinterability is unlikely to decrease during sintering of the positive electrode active material precursor, and deterioration of battery characteristics is unlikely to occur. In addition, since the sinterability is unlikely to decrease during sintering of the positive electrode active material precursor, the electrode layer 1 can be made thicker, and the charge / discharge capacity of the resulting secondary battery can be increased.

[0034] Therefore, according to the electrode material for secondary batteries of the present invention, it is possible to achieve both high levels of electronic conductivity and high levels of ionic conductivity, and it is possible to effectively improve the battery characteristics.

[0035] The electrode material for secondary batteries of the present invention preferably contains, by mass%, 30% to 98% of a positive electrode active material, 0.1% to 65% of a solid electrolyte, and 0.1% to 3% of a conductive additive, whereby electronic conductivity and ionic conductivity can be simultaneously achieved at higher levels, and battery characteristics can be effectively improved.

[0036] In the present invention, the content of the positive electrode active material in the electrode mixture for secondary batteries is, in mass %, preferably 30% or more, more preferably 50% or more, and even more preferably 70% or more, and is preferably 98% or less, and more preferably 95% or less. When the content of the positive electrode active material in the electrode mixture for secondary batteries is within the above range, the battery characteristics such as the charge and discharge capacity of the secondary battery can be more effectively improved.

[0037] In the present invention, the content of the solid electrolyte in the electrode mixture for secondary batteries is, in mass %, preferably 0.1% or more, more preferably 5% or more, even more preferably 8% or more, and is preferably 65% ​​or less, more preferably 40% or less, even more preferably 30% or less, and particularly preferably 20% or less. When the content of the solid electrolyte in the electrode mixture for secondary batteries is within the above range, the ion conductivity can be further improved, and the battery characteristics can be further improved effectively.

[0038] In the present invention, the content of the conductive assistant in the electrode mixture for secondary batteries is, in mass%, preferably 0.1% or more, more preferably 0.2% or more, even more preferably 0.3% or more, particularly preferably 0.4% or more, most preferably 0.5% or more, preferably 3% or less, more preferably 2% or less, even more preferably 1% or less, still more preferably 0.9% or less, particularly preferably 0.8% or less, and most preferably 0.7% or less. When the conductive assistant in the electrode mixture for secondary batteries contains sheet carbon and the content of the conductive assistant is within the above range, it is possible to further improve ion conductivity while ensuring high electronic conductivity, and to further effectively improve battery characteristics.

[0039] In the present invention, the ratio of the content of the conductive assistant to the positive electrode active material (conductive assistant / positive electrode active material) is preferably 0.001 or more, more preferably 0.002 or more, even more preferably 0.003 or more, particularly preferably 0.004 or more, most preferably 0.005 or more, preferably 0.05 or less, more preferably 0.03 or less, even more preferably 0.02 or less, even more preferably 0.01 or less, particularly preferably 0.009 or less, and most preferably 0.007 or less. When the conductive assistant in the electrode mixture for secondary batteries contains sheet carbon and the content ratio (conductive assistant / positive electrode active material) is within the above range, it is possible to further improve ion conductivity while ensuring high electronic conductivity, and to further effectively improve battery characteristics.

[0040] The above content ratio (conductive assistant / positive electrode active material) can be determined by dividing the content (mass%) of the conductive assistant in the electrode mixture for a secondary battery by the content (mass%) of the positive electrode active material in the electrode mixture for a secondary battery.

[0041] In the present invention, the surface area ratio of the conductive assistant to the positive electrode active material (conductive assistant / positive electrode active material) is preferably 0.01 or more, more preferably 0.02 or more, even more preferably 0.03 or more, particularly preferably 0.04 or more, most preferably 0.05 or more, preferably 1.2 or less, more preferably 1.0 or less, even more preferably 0.9 or less, even more preferably 0.8 or less, particularly preferably 0.7 or less, and most preferably 0.6 or less. When the conductive assistant in the electrode mixture for secondary batteries contains sheet carbon and the surface area ratio (conductive assistant / positive electrode active material) is within the above range, it is possible to further improve ion conductivity while ensuring high electronic conductivity, and to further effectively improve battery characteristics.

[0042] The surface area ratio (conductive assistant / positive electrode active material) is calculated by the following formula (1).

[0043] Surface area ratio = (A1×A2) / (B1×B2)…Equation (1)

[0044] In formula (1), A1 is the content (mass%) of the conductive additive in the electrode mixture for a secondary battery. A2 is the BET specific surface area (m 2 / g). B1 is the content (mass%) of the positive electrode active material in the electrode mixture for secondary batteries. B2 is the BET specific surface area (m 2 The BET specific surface area of ​​the conductive additive and the positive electrode active material can be measured by a multipoint BET method using nitrogen as an adsorbate.

[0045] The electrode mixture for secondary batteries of the present invention is preferably used in sodium ion secondary batteries, and more preferably used in all-solid-state sodium ion secondary batteries.

[0046] Specific examples of the materials constituting the secondary battery electrode mixture of the present invention will be described below.

[0047] (Cathode active material) The positive electrode active material contains (i) at least one transition metal element selected from the group consisting of Cr, Fe, Mn, Co, Ni, Ti, and Nb, (ii) at least one element selected from the group consisting of P, Si, and B, and (iii) an element consisting of O.

[0048] In the present invention, the positive electrode active material is represented by the general formula A x MC y O z (A is at least one selected from the group consisting of Li and Na, M is at least one selected from the group consisting of Cr, Fe, Mn, Co and Ni, C is at least one selected from the group consisting of P, Si and B, 0.2≦x≦4.2, 0.65≦y≦6.5 and 2.5≦z≦20), and preferably contains a crystal represented by the general formula A x MC y O z (A is at least one selected from the group consisting of Li and Na, M is at least one selected from the group consisting of Cr, Fe, Mn, and Co, C is at least one selected from the group consisting of P, Si, and B, and 0.2≦x≦4.2, 0.65≦y≦6.5, and 2.5≦z≦20) is more preferable.

[0049] The positive electrode active material is represented by the general formula Na x M y P2O z (1≦x≦2.8, 0.95≦y≦1.6, 6.5≦z≦8, M is at least one selected from the group consisting of Cr, Fe, Mn, Co, and Ni) is preferable. In particular, the positive electrode active material is made of crystallized glass containing crystals represented by the general formula Na x It is more preferable that the positive electrode active material is made of crystallized glass containing crystals represented by MP2O7 (1≦x≦2, M is at least one selected from the group consisting of Cr, Fe, Mn, Co, and Ni).

[0050] Examples of the crystals contained in the positive electrode active material include NaFeP0 and NaCoP0. 7、Na2NiP2O7, etc. can be used.

[0051] In the present disclosure, crystallized glass means a precursor glass containing an amorphous phase is heated (fired) to precipitate (crystallize) crystals. The entire amorphous phase may be transformed into a crystalline phase, or the amorphous phase may remain. Also, one type of crystal may be precipitated, or two or more types of crystals may be precipitated. For example, it is possible to determine whether crystallized glass is crystallized glass or not by the peak angle and peak intensity shown by powder X-ray diffraction (XRD).

[0052] (solid electrolyte) The solid electrolyte is a component responsible for ion conduction in the electrode layer of an all-solid-state secondary battery. By including a solid electrolyte, the ion conductivity of the electrode material for a secondary battery can be increased even without an electrolytic solution.

[0053] The solid electrolyte is preferably formed from a sodium ion conductive oxide. Examples of the sodium ion conductive oxide include compounds containing at least one selected from Al, Y, Zr, Si, and P, Na, and O. Specific examples of the sodium ion conductive oxide include beta-alumina or NASICON type crystal, which have excellent sodium ion conductivity. In particular, the sodium ion conductive oxide is preferably at least one sodium ion conductive oxide selected from the group consisting of β''-alumina, β-alumina, and NASICON type crystal. The sodium ion conductive oxide is more preferably β-alumina or β''-alumina. These have even better sodium ion conductivity.

[0054] Beta alumina has two crystal forms: β-alumina (theoretical formula: Na2O·11Al2O3) and β''-alumina (theoretical formula: Na2O·5.3Al2O3). β''-alumina is a metastable substance, so it is usually used with Li2O or MgO added as a stabilizer. β''-alumina has a higher sodium ion conductivity than β-alumina, so it is preferable to use β''-alumina alone or a mixture of β''-alumina and β-alumina, and Li2O-stabilized β''-alumina (Na 1.7 Li 0.3 Al 10.7 O 17 ) or MgO-stabilized β''-alumina ((Al 10.32 Mg 0.68 O 16 )(Na 1.68 It is more preferable to use O).

[0055] NASICON type crystals include Na3Zr2Si2PO 12 , Na 3.2 Zr 1.3 S 2.2 P 0.8 O 10.5 , Na3Zr 1.6 Ti 0.4 SiPO 12 , Na3Hf2Si2PO 12 , Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 S 1.2 P 1.8 O 12 , Na3Zr 1.7 Nb 0.24 SiPO 12 , Na 3.6 Ti 0.2 Y 0.8 S 2.8 O9, Na3Zr 1.88 Y 0.12 SiPO 12 , Na 3.12 Zr 1.88 Y 0.12 SiPO 12 , Na 3.05 Zr2Si 2.06 P 0.95 O12 , Na 3.4 Zr2Si 2.4 P 0.6 O 12 , Na 3.4 Zr 1.9 Mg 0.1 S 2.4 P 0.6 O 12 , Na 3.4 Zr 1.9 Zinc 0.1 S 2.4 P 0.6 O 12 , Na 3.4 Zr 1.9 Mg 0.1 S 2.2 P 0.8 O 12 , Na 3.4 Zr 1.9 Zinc 0.1 S 2.2 P 0.8 O 12 , Na 3.6 Zr 0.13 Yb 1.67 S 0.11 P 2.9 O 12 , Na5YSi4O 12 Among them, NASICON type crystals are 3.4 Zr2Si 2.4 P 0.6 O 12 Or Na 3.05 Zr2Si 2.06 P 0.95 O 12 In this case, the sodium ion conductivity can be further improved.

[0056] (Conductive assistant) The conductive assistant is a component that forms a conductive path in the electrode layer. In the present invention, the conductive assistant contains sheet carbon. This makes it easy to achieve both high electronic conductivity and high ionic conductivity as an electrode mixture for a secondary battery even with a small amount of the conductive assistant. The conductive assistant is preferably made of only sheet carbon. Examples of the sheet carbon include graphene or reduced graphene oxide. In particular, the sheet carbon preferably contains graphene, and more preferably consists of graphene. It is even more preferable that the conductive assistant consists of graphene. The number of layers of graphene is not particularly limited, and may be one layer or two or more layers.

[0057] The BET specific surface area of ​​the sheet carbon is preferably 100 m 2 / g or more, more preferably 300m 2 / g or more, more preferably 500m 2 The upper limit of the BET specific surface area of ​​the sheet carbon is not particularly limited, but is preferably 5000 m 2 / g or less, more preferably 4000m 2 / g or less, more preferably 3000m 2 / g or less. When the BET specific surface area of ​​the sheet carbon is within the above range, the electronic conductivity of the electrode composite for secondary batteries can be further increased with a smaller amount of addition. The BET specific surface area of ​​the sheet carbon can be measured by a multipoint BET method using nitrogen as an adsorbate.

[0058] The length of the sheet carbon is preferably 0.5 μm or more, more preferably 1 μm or more, even more preferably 3 μm or more, and preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. The thickness of the sheet carbon is preferably 1 nm or more, more preferably 3 nm or more, preferably 30 nm or less, and more preferably 20 nm or less. When the length and thickness of the sheet carbon are within the above ranges, the electronic conductivity of the electrode mixture for secondary batteries can be further increased with a smaller amount of the sheet carbon added.

[0059] The length and thickness of the sheet carbon can be calculated, for example, by measuring the lengths and thicknesses of 200 pieces of sheet carbon using a scanning electron microscope or the like and averaging the measured values.

[0060] [Electrodes for all-solid-state secondary batteries and all-solid-state secondary batteries] Fig. 2 is a schematic cross-sectional view showing an all-solid-state secondary battery according to one embodiment of the present invention. As shown in Fig. 2, an all-solid-state secondary battery 21 includes a solid electrolyte layer 22, a positive electrode layer (electrode layer) 23, a negative electrode layer 24, a first current collector layer 25, and a second current collector layer 26. In this embodiment, the all-solid-state secondary battery is an all-solid-state sodium ion secondary battery.

[0061] The solid electrolyte layer 22 has a first main surface 22a and a second main surface 22b facing each other. A positive electrode layer 23 is provided on the first main surface 22a of the solid electrolyte layer 22. A first current collector layer 25 is provided on the main surface of the positive electrode layer 23 opposite to the solid electrolyte layer 22. A negative electrode layer 24 is provided on the second main surface 22b of the solid electrolyte layer 22. A second current collector layer 26 is provided on the main surface of the negative electrode layer 24 opposite to the solid electrolyte layer 22. The first current collector layer 25 and the second current collector layer 26 may not be provided. The electrode for an all-solid-state secondary battery of the present invention refers to, for example, the positive electrode layer 23.

[0062] Hereinafter, each layer in the all-solid-state secondary battery 21 of the present invention will be described in detail.

[0063] (Positive electrode layer) The positive electrode layer 23 is composed of the electrode mixture for secondary batteries of the present invention described above. The positive electrode layer 23 (electrode mixture for secondary batteries) can be formed, for example, by forming an electrode material layer containing a positive electrode active material precursor, a conductive assistant, and, if necessary, a sodium ion conductive solid electrolyte powder on the first main surface 22a of the solid electrolyte layer 22, and firing the electrode material layer. The electrode material layer can be obtained, for example, by applying a paste containing a positive electrode active material precursor, a conductive assistant, and, if necessary, a solid electrolyte powder, and drying the paste. The paste may contain a binder, a plasticizer, a solvent, or the like, if necessary. The electrode material layer may be a powder compact.

[0064] The drying temperature of the paste is not particularly limited, but may be, for example, 30° C. or more and 150° C. or less. The drying time of the paste is not particularly limited, but may be, for example, 5 minutes or more and 600 minutes or less.

[0065] The firing atmosphere is preferably an inert atmosphere or a reducing atmosphere. The firing temperature (maximum temperature) can be, for example, 400° C. to 800° C., and the holding time at that temperature can be, for example, 5 minutes to less than 3 hours.

[0066] Positive electrode active material precursor; The positive electrode active material precursor (positive electrode active material precursor powder) is preferably made of an amorphous oxide material that generates active material crystals by firing. When the positive electrode active material precursor powder is made of an amorphous oxide material, active material crystals are generated during firing, and the material softens and flows to form a dense positive electrode layer 23. In addition, firing can also integrate the positive electrode active material of the positive electrode layer 23 with the solid electrolyte. Furthermore, firing can integrate the positive electrode layer 23 with the solid electrolyte layer 22. As a result, an ion conduction path is more favorably formed, which is preferable. In addition, in the present invention, the "amorphous oxide material" is not limited to a completely amorphous oxide material, but also includes one that contains some crystals (for example, a crystallinity of 10% or less).

[0067] The positive electrode active material precursor powder preferably contains, in mole percent calculated as the following oxides, 10% to 55% Na2O, 10% to 50% Fe2O3+Cr2O3+MnO+CoO+NiO, and 15% to 70% P2O5. The reason for limiting the composition in this way is explained below. In the following explanation of the content of each component, "%" means "mol percent" unless otherwise specified.

[0068] Na2O has the general formula Na x M y P2O z (M is at least one transition metal element selected from the group consisting of Cr, Fe, Mn, Co, and Ni, and is a main component of the active material crystal represented by 1≦x≦2.8, 0.95≦y≦1.6, and 6.5≦z≦8). The Na2O content is preferably 10% to 55%, more preferably 15% to 50%, and even more preferably 30% to 50%. When the Na2O content is within the above range, the charge / discharge capacity can be further increased.

[0069] Fe2O3, Cr2O3, MnO, CoO and NiO also have the general formula Na x M y P2O zIt is the main component of the active material crystal represented by the formula: Fe2O3+Cr2O3+MnO+CoO+NiO content is preferably 10% to 50%, more preferably 15% to 30%, and even more preferably 15% to 25%. When the content of Fe2O3+Cr2O3+MnO+CoO+NiO is equal to or greater than the lower limit, the charge / discharge capacity can be further increased. On the other hand, when the content of Fe2O3+Cr2O3+MnO+CoO+NiO is equal to or less than the upper limit, it is possible to make it difficult for undesired crystals such as Fe2O3, Cr2O3, MnO, CoO, or NiO to precipitate. In order to further improve the cycle characteristics, it is preferable to actively include Fe2O3. The content of Fe2O3 is preferably 1% to 50%, more preferably 5% to 40%, even more preferably 10% to 30%, and particularly preferably 15% to 25%. The content of each of the components Cr2O3, MnO, CoO and NiO is preferably 0% to 30%, more preferably 10% to 30%, and even more preferably 15% to 25%. When at least two or more components selected from the group consisting of Fe2O3, Cr2O3, MnO, CoO and NiO are contained, the total content thereof is preferably 10% to 50%, more preferably 10% to 30%, and even more preferably 15% to 25%.

[0070] P2O5 also has the general formula Na x M y P2O z It is the main component of the active material crystal represented by the formula: The content of P2O5 is preferably 15% to 70%, more preferably 25% to 55%, and further preferably 30% to 50%. When the content of P2O5 is within the above range, the charge / discharge capacity can be further increased.

[0071] The positive electrode active material precursor powder may contain V2O5, Nb2O5, MgO, Al2O3, TiO2, ZrO2, or Sc2O3 in addition to the above components. These components have the effect of increasing electrical conductivity (electronic conductivity), and the high-speed charge / discharge characteristics are likely to be improved. The total content of the above components is preferably 0% to 25%, and more preferably 0.2% to 10%. When the content of the above components is equal to or less than the upper limit, heterogeneous crystals that do not contribute to the battery characteristics are unlikely to be generated, and the charge / discharge capacity can be further increased.

[0072] In addition to the above components, the positive electrode active material precursor powder may contain SiO2, B2O3, GeO2, Ga2O3, Sb2O3, or Bi2O3. By containing these components, the glass forming ability is further improved, and it becomes easier to obtain a more homogeneous positive electrode active material precursor powder. The total content of the above components is preferably 0% to 37%, and more preferably 0.2% to 25%. Since these components do not contribute to the battery characteristics, if the content is too high, the charge / discharge capacity tends to decrease.

[0073] The positive electrode active material precursor powder is preferably produced by melting and molding a raw material batch. This method is preferable because it is easy to obtain an amorphous positive electrode active material precursor powder with excellent homogeneity. Specifically, the positive electrode active material precursor powder can be produced as follows.

[0074] First, the raw materials are prepared to have a desired composition to obtain a raw material batch. Next, the obtained raw material batch is melted. The melting temperature may be appropriately adjusted so that the raw material batch is homogeneously melted. For example, the melting temperature is preferably 800°C or higher, and more preferably 900°C or higher. There is no particular limit to the upper limit of the melting temperature, but since a melting temperature that is too high leads to energy loss and evaporation of sodium components, etc., it is preferably 1500°C or lower, and more preferably 1400°C or lower.

[0075] Next, the obtained molten material is molded by any method, and for example, the molten material may be poured between a pair of cooling rolls and molded into a film while being rapidly cooled, or the molten material may be poured into a mold and molded into an ingot.

[0076] The resulting molded body is then pulverized to obtain a positive electrode active material precursor powder. The positive electrode active material precursor powder has an average particle size of preferably 0.01 μm or more and less than 5 μm, more preferably 0.03 μm or more and 3 μm or less, even more preferably 0.03 μm or more and 2 μm or less, particularly preferably 0.03 μm or more and 1 μm or less, and most preferably 0.03 μm or more and 0.7 μm or less.

[0077] In the present invention, the average particle size is D 50 (volume-based median diameter) and indicates a value measured by a laser diffraction scattering method.

[0078] solid electrolyte powder; The solid electrolyte powder is obtained by, for example, pulverizing the above solid electrolyte. The average particle diameter of the solid electrolyte powder is preferably 0.01 μm or more and 3 μm or less, more preferably 0.03 μm or more and less than 1.8 μm, even more preferably 0.03 μm or more and 1.5 μm or less, particularly preferably 0.03 μm or more and 1.2 μm or less, and most preferably 0.03 μm or more and 0.7 μm or less. If the average particle diameter of the solid electrolyte powder is too small, not only is it difficult to mix it uniformly with the active material precursor powder, but there is also a risk that the ion conductivity will decrease due to moisture absorption or carbonation, or that excessive reaction with the active material precursor powder will be promoted. As a result, the internal resistance of the electrode material layer will tend to increase, and the voltage characteristics and charge / discharge capacity will tend to decrease. On the other hand, if the average particle diameter of the solid electrolyte powder is too large, the softening and flow of the active material precursor powder will be significantly hindered, so that the smoothness of the obtained electrode layer will be inferior, the mechanical strength will decrease, and the internal resistance will tend to increase.

[0079] binder; Binders are materials for integrating raw materials (raw material powders) together. Examples of binders include cellulose derivatives such as carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and hydroxymethyl cellulose, water-soluble polymers such as polyvinyl alcohol, thermosetting resins such as thermosetting polyimide, phenol resin, epoxy resin, urea resin, melamine resin, unsaturated polyester resin, and polyurethane, polycarbonate resins such as polypropylene carbonate, and polyvinylidene fluoride.

[0080] The thickness of the positive electrode layer 23 is preferably 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, particularly preferably 70 μm or more, and most preferably 100 μm or more. In this case, the charge / discharge capacity of the all-solid-state secondary battery can be further increased. On the other hand, if the thickness of the positive electrode layer 23 is too thick, the resistance to electronic conduction increases, which may reduce the discharge capacity and operating voltage, and the stress due to shrinkage during firing increases, which may lead to peeling, so the thickness is preferably 1000 μm or less.

[0081] The amount of the positive electrode active material carried in the positive electrode layer 23 is preferably 1 mg / cm 2 More preferably, 3 mg / cm 2 More preferably, 5 mg / cm 2 More preferably, 7 mg / cm 2 More than 10 mg / cm, most preferably 10 mg / cm 2 In this case, the charge / discharge capacity of the all-solid-state secondary battery can be further increased. The upper limit of the amount of the positive electrode active material carried is not particularly limited, but is, for example, 500 mg / cm. 2 It can be said that:

[0082] (Solid electrolyte layer) The solid electrolyte layer 22 can be manufactured by mixing raw material powders (solid electrolyte powders), molding the mixed raw material powders (solid electrolyte powders), and then firing the molded product. For example, the raw material powders (solid electrolyte powders) are slurried to produce a green sheet, and the green sheet is then fired. The solid electrolyte layer 22 can also be manufactured by a sol-gel method. Furthermore, the solid electrolyte layer can be formed on a solid electrolyte substrate having a thickness in the range of 0.1 to 3 mm.

[0083] The average particle size of the solid electrolyte powder is preferably 0.01 μm or more and 3 μm or less, more preferably 0.03 μm or more and less than 1.8 μm, even more preferably 0.03 μm or more and 1.5 μm or less, particularly preferably 0.03 μm or more and 1.2 μm or less, and most preferably 0.03 μm or more and 0.7 μm or less. If the average particle size of the solid electrolyte powder is too small, there is a risk of the ion conductivity decreasing due to moisture absorption or carbonation. As a result, the internal resistance of the electrode material layer increases, and the voltage characteristics and charge / discharge capacity tend to decrease. On the other hand, if the average particle size of the solid electrolyte powder is too large, the internal resistance tends to increase.

[0084] The thickness of the solid electrolyte layer 22 is preferably 5 μm or more and 1000 μm or less, and more preferably 10 μm or more and 200 μm or less. If the thickness of the solid electrolyte layer 22 is too thin, the mechanical strength decreases and the layer becomes more susceptible to breakage, which makes it more likely to cause an internal short circuit. If the thickness of the solid electrolyte layer 22 is too thick, the sodium ion conduction distance associated with charging and discharging becomes longer, which increases the internal resistance, and the discharge capacity and operating voltage of the secondary battery tend to decrease. In addition, the energy density per unit volume of the secondary battery also tends to decrease.

[0085] (Negative electrode layer) The negative electrode active material contained in the negative electrode layer 24 is not particularly limited, and may be, for example, a carbon electrode material such as hard carbon or soft carbon. The carbon electrode material is preferably hard carbon. However, the negative electrode active material may contain an alloy-based negative electrode active material capable of absorbing sodium, such as tin, bismuth, lead, or phosphorus, or metallic sodium. It is preferable that the negative electrode layer 24 is not a negative electrode layer made of a single phase of metallic sodium.

[0086] The negative electrode layer 24 may further contain a sodium ion conductive solid electrolyte and a conductive assistant. The ratio of each material in the negative electrode layer 24 may be, for example, in mass %, 60% to 100% of the negative electrode active material, 0% to 35% of the sodium ion conductive solid electrolyte, and 0% to 5% of the conductive assistant. The sodium ion conductive solid electrolyte may be, for example, the above-mentioned solid electrolyte. The conductive assistant may be, for example, the above-mentioned conductive assistant.

[0087] The thickness of the negative electrode layer 24 is preferably 0.3 μm or more and 500 μm or less, and more preferably 3 μm or more and 300 μm or less. If the thickness of the negative electrode layer 24 is too thin, the absolute capacity (mAh / g) of the negative electrode tends to decrease. If the thickness of the negative electrode layer 24 is too thick, the resistance increases, and the capacity (mAh / g) tends to decrease.

[0088] The negative electrode layer 24 can be prepared, for example, by using a slurry containing a negative electrode active material precursor powder and, if necessary, a solid electrolyte powder or a conductive assistant. If necessary, a binder, a plasticizer, a solvent, and the like are added to the slurry. The negative electrode layer 24 can be prepared by applying the slurry onto the second main surface 22b of the solid electrolyte layer 22, drying the slurry, and firing the slurry. The negative electrode layer 24 may also be prepared by applying the slurry onto a substrate such as PET (polyethylene terephthalate), drying the slurry, preparing a green sheet, and firing the green sheet. Alternatively, the negative electrode layer 24 may be made of a metal, and in this case, the negative electrode layer 24 can be prepared by a sputtering method, a vapor deposition method, or the like.

[0089] (First current collector layer and second current collector layer) The materials of the first current collector layer 25 and the second current collector layer 26 are not particularly limited, but may be metal materials such as aluminum, titanium, silver, copper, stainless steel, or alloys thereof. The above metal materials may be used alone or in combination. These alloys are alloys containing at least one of the above metals. The thicknesses of the first current collector layer 25 and the second current collector layer 26 are not particularly limited, but may be 0.01 μm or more and 1000 μm or less, respectively.

[0090] The method for forming the first current collector layer 25 and the second current collector layer 26 is not particularly limited, and examples thereof include physical vapor phase methods such as vapor deposition or sputtering, and chemical vapor phase methods such as thermal CVD, MOCVD, and plasma CVD. Other methods for forming the first current collector layer 25 and the second current collector layer 26 include liquid phase film formation methods using plating, a sol-gel method, and spin coating. However, it is preferable to form the first current collector layer 25 and the second current collector layer 26 on the positive electrode layer 23 and the negative electrode layer 24, respectively, by a sputtering method, because this provides excellent adhesion.

[0091] In the above embodiment, an all-solid-state sodium ion secondary battery using a material having sodium ion conductivity has been described. However, the electrode composite for a secondary battery of the present invention may be used for other all-solid-state secondary batteries, such as an all-solid-state lithium ion secondary battery using a material having lithium ion conductivity.

[0092] The present invention will be described in more detail below with reference to specific examples. The present invention is not limited to the following examples, and can be modified as appropriate within the scope of the present invention.

[0093] Example 1 (a) Preparation of solid electrolyte layer β''-alumina (1 mm thick, 12 mm square) manufactured by Ionotec was used as the solid electrolyte substrate. The raw materials were mixed to obtain the β''-alumina composition, calcined at 1250°C, and pulverized. The calcined raw materials, binder, plasticizer, dispersant, solvent, etc. were mixed to produce a paste. The paste was applied to the aforementioned β''-alumina substrate to a thickness of 100 μm and a size of 10 mm square. After drying in a constant temperature bath at 70°C for 2 hours, it was fired at 1550°C for 30 minutes to form a solid electrolyte layer of 10 mm square and 100 μm thick on the solid electrolyte substrate.

[0094] (b) Preparation of positive electrode paste The glass composition was 40Na2O-20Fe2O3-40P2O5 in molar ratio. The raw materials were melted at 1250°C for 45 minutes in air and cooled. The glass film was then formed using a twin roller. The glass film was then pulverized using a ball mill and a planetary ball mill to produce a glass film with an average particle size D50 of 0.2 μm and a BET specific surface area of ​​30 m. 2 / g of a positive electrode active material precursor powder (glass powder) was obtained.

[0095] The obtained glass powder (86.9 mass%) and β''-alumina (specific surface area: 45 m) were used as a solid electrolyte. 2 / g) 12.9 mass%, and graphene (manufactured by Jikan Techno Co., Ltd., multi-layer biomass nanocarbon, BET specific surface area: 750 m) as a conductive additive. 2 0.2 mass% of 1000g / g, thickness: 1-3 nm, length: 30 μm) was mixed to prepare a positive electrode composite powder. 20 mass% of polypropylene carbonate (PPC) was added as a binder to 100 mass% of the obtained positive electrode composite powder, and N-methyl-2-pyrrolidone was added as a solvent so that the concentration of the positive electrode composite powder was 50 mass%. This was mixed in a planetary mixer to prepare a positive electrode paste.

[0096] (c) Formation of the positive electrode The positive electrode paste was applied to the center of the main surface of the solid electrolyte layer to a thickness of 100 μm and a square of 10 mm. After drying for 2 hours in a thermostatic chamber at 80°C, it was fired in an N2 / H2 (96 / 4 vol%) atmosphere at 500°C for 30 minutes to form an electrode composite for secondary batteries (positive electrode).

[0097] (d) Formation of current collector and assembly of coin cell A 100 nm thick gold film was deposited as a current collector on the entire surface of the positive electrode. After that, in an argon glove box, metallic sodium was attached as a negative electrode to the main surface of the solid electrolyte layer opposite the positive electrode, and the cell was sealed in a CR2032 coin cell to produce an all-solid-state battery.

[0098] (Example 2, Example 3 and Comparative Example 1) An all-solid-state secondary battery was produced in the same manner as in Example 1, except that the composition of the electrode composite material for secondary batteries was adjusted to the composition in Table 1 below. In Comparative Example 1, acetylene black (manufactured by Timcal Corporation, product number "SUPER P", BET specific surface area: 62 m) was used as a conductive assistant. 2 / g) was used.

[0099] [evaluation] The fabricated battery was charged at 30°C and 0.02C, and the initial discharge capacity (hereinafter referred to as discharge capacity) was measured at 30°C and at rates of 0.02C, 2C, and 10C. The battery characteristics were measured by calculating the ratio of the discharge capacity at 2C rate to the discharge capacity at 0.02C rate, and the ratio of the discharge capacity at 10C rate to the discharge capacity at 0.02C rate. The results are shown in Table 1 below.

[0100] [Table 1]

[0101] Thus, in the graphene content range of 0.2 mass% to 2.0 mass% (Examples 1 to 3), the ratio of the discharge capacity at 2C rate to the discharge capacity at 0.02C rate (2C discharge capacity ratio) was 40% or more, and the ratio of the discharge capacity at 10C rate to the discharge capacity at 0.02C rate (10C discharge capacity ratio) was high, 15% or more, and particularly, in the graphene content of 0.2 mass% (Example 1), the 2C discharge capacity ratio was 70% and the 10C discharge capacity ratio was 50%, which were higher. On the other hand, in Comparative Example 1 in which acetylene black was used as the conductive assistant, the 2C discharge capacity ratio was high at 63%, but the 10C discharge capacity ratio was low at 0%. [Explanation of symbols]

[0102] 1...Electrode layer 2...Solid electrolyte layer 3...Cathode active material 4...Solid electrolyte 5...Conductive assistant 21…All-solid-state secondary battery 22...Solid electrolyte layer 22a, 22b...first and second principal surfaces 23...Positive electrode layer 24...Negative electrode layer 25, 26...First and second current collector layers

Claims

1. A positive electrode active material and a conductive assistant, The positive electrode active material contains (i) at least one transition metal element selected from the group consisting of Cr, Fe, Mn, Co, Ni, Ti, and Nb, (ii) at least one element selected from the group consisting of P, Si, and B, and (iii) an element consisting of O; The electrode mixture for a secondary battery, wherein the conductive assistant comprises sheet-like carbon.

2. The electrode mixture for a secondary battery according to claim 1 , wherein the conductive assistant consists of sheet-like carbon alone.

3. The electrode mixture for a secondary battery according to claim 1 or 2, wherein the sheet carbon contains graphene.

4. The electrode mixture for a secondary battery according to claim 1 or 2, wherein the sheet carbon consists of graphene alone.

5. The positive electrode active material is represented by the general formula A x M.C. y O z 3. The electrode mixture for a secondary battery according to claim 1, comprising a crystal represented by the formula: (A is at least one selected from the group consisting of Li and Na, M is at least one selected from the group consisting of Cr, Fe, Mn, Co and Ni, C is at least one selected from the group consisting of P, Si and B, and 0.2≦x≦4.2, 0.65≦y≦6.5 and 2.5≦z≦20).

6. The electrode mixture for a secondary battery according to claim 1 or 2, wherein the positive electrode active material further contains Na.

7. The electrode mixture for a secondary battery according to claim 1 or 2, further comprising a solid electrolyte.

8. The electrode mixture for secondary batteries according to claim 7, wherein the solid electrolyte contains β-alumina, β″-alumina, or NASICON type crystals.

9. 3. The electrode mixture for a secondary battery according to claim 1 or 2, comprising, in mass%, 30% to 98% of the positive electrode active material, 0.1% to 65% of a solid electrolyte, and 0.1% to 3% of the conductive assistant.

10. 3. The electrode mixture for a secondary battery according to claim 1, wherein a ratio of the content of the conductive assistant to the positive electrode active material (conductive assistant / positive electrode active material) is 0.001 or more and 0.05 or less in mass ratio.

11. 3. The electrode mixture for a secondary battery according to claim 1, wherein a ratio of a surface area of ​​the conductive assistant to the positive electrode active material (conductive assistant / positive electrode active material) is 0.01 or more and 0.5 or less.

12. The electrode mixture for a secondary battery according to claim 1 or 2, which is for a sodium ion secondary battery.

13. The electrode mixture for a secondary battery according to claim 1 or 2, which is for an all-solid-state sodium ion secondary battery.

14. An electrode for an all-solid-state secondary battery, comprising the electrode mixture for a secondary battery according to claim 1 or 2.

15. An all-solid-state secondary battery comprising the electrode for an all-solid-state secondary battery according to claim 14 as a positive electrode.

Citation Information

Patent Citations

  • Method for manufacturing positive electrode material for electrical storage device

    WO2016084573A1